Pengaruh Budaya Organisasi Terhadap Komitmen Organisasi dan Kinerja Karyawan Dinas Kesehatan Kabupaten Lampung Selatan - Erdi, Hery; Bambang, R; Kulsum, Umi (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
Human resources have a strategic role, including in the South Lampung District Health Office. Preliminary research implies that the employee performance of the Office is still not optimal. This study aims to examine the influence of organizational culture on organizational commitment and employee performance at the South Lampung District Health Office, considering research on how to improve employee performance in public institutions is still limited. This study uses a survey method to collect the relevant data to the research objectives. The sample involved in the study were 97 employees who were randomly selected from a population of 128 employees. The data were analyzed using the Structural Equation Modeling. The findings indicate that organizational culture has a significant positive effect on employee performance (β = 0.40; p <0.01), in addition to having a significant and positive effect on employee commitment (β = 0.22; p <0.05). . In addition, it was found that organizational commitment has a positive effect on employee performance (β = 0.28; p <0.05). The findings suggest the importance of the Office to build an organizational culture through four dimensions, namely competitive culture, entrepreneurial culture, bureaucratic culture, and consensual culture. This approach will strengthen affective commitment, ongoing commitment, and normative commitment. Keywords: employee performance, organizational culture, organizational commitment, south lampung district health office